Peningkatan Efektivitas Social Entrepreneurship Dalam Mengatasi Tantangan Keberlanjutan Studi Kasus Pada PT Pertamina (Persero) - Marsel Pasaribu; Ricky Agusiady; Fitriana (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study aims to analyze and improve the effectiveness of social entrepreneurship practices implemented by PT Pertamina (Persero) in facing sustainability challenges. As global pressure on environmental, social, and economic issues increases, the role of companies in supporting sustainable development is becoming increasingly crucial. Through a qualitative approach with a case study method, this study explores the implementation of social entrepreneurship programs integrated into corporate social responsibility (CSR) activities. Data collection techniques were carried out through in-depth interviews, field observations, and documentation studies of various MSME development programs, social entrepreneurship training, and multi-stakeholder collaborations implemented by PT Pertamina The research results indicate that the social entrepreneurship program has had a positive impact in increasing community economic capacity and promoting environmental awareness. However, several challenges were identified, such as limited market access, post-intervention program sustainability, and a suboptimal long-term impact-based evaluation system. This study recommends strengthening the monitoring and evaluation system, increasing cross-sector synergy, and integrating sustainability strategies throughout the social program value chain. These improvements can maximize the effectiveness of social entrepreneurship as a solution to sustainability challenges.